Dampak Artificial Intelligence Terhadap Profesi Akuntan - Fauzi, Rizki; Indriani, Rini (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2023)
The development of Artificial Intelligence has changed the way accountants work.. This study reviews the latest advancements in Artificial Intelligence, Big Data, and Machine Learning and how they are used in accounting for businesses around the world. The writer looks at how accounting has changed over time because of new technology. They also study how big companies use technology and how it will continue to affect accounting. Also, the study used a method that described and explained things in detail. The researcher looked at information from previous studies to learn more about a topic. This study looks at how accountants use new technology and discusses what the accounting profession needs to do to get ready for the future.